Trees and anthills: songs of Karimojong women's groups - Gourlay, Ken A. (International Library of African Music, 1970)
Karamoja District of north-eastern Uganda is a semi-arid plateau between 3,000 and 4,000 feet high. Most of its 9,230 square miles is covered with sparse savannah grassland or stunted acacia shrubs. Beside the dry, sandy river beds grow larger trees of the acacia family. Except for the areas of no-man's land between rival groups, the entire region suffers from over-grazing by cattle. In the settled areas even the largest trees have been hacked and hewn for firewood. For half the year the sun scorches the unprotected earth into the harness of concrete. When the rains come water flows quickly away before the soil can absorb it, and the rivers fill up in flash floods that sweep away even the tallest trees.
Keywords: Ethnomusicology; Women; Karamojong (African people); Uganda; African Music